Hubungan Tingkat Pengetahuan Tentang Kusta (Leprosy) dengan Perawatan Diri Pada Penderita Kusta di Wilayah Kabupaten Sukoharjo - Solikhah, Amaliatus; , Agus Sudaryanto, S.Kep., Ns., M.Kes; , Vinami Yulian, S. Kep. , Ns (2016)
ABSTRACT Leprosy is one of 17 tropical disease which are still ignored tropical diseases that ignored with incidence rates that are still high. The disease generally will attack skin and nervous system. The involvement and nerve damage can cause disability and paralysis of the hands, feet and eyes. Patients should understand that the treatment of MDT can kill leprosy bacteria, but defects eye, hand or feet which already occurred will remain there for the rest of life, so it would take care of themselves diligently so that his disability did not get worse. The principle of self-care are essentially in 3 steps, step 1 is checking eyes, hands, and feet regularly, step 2 is protect the eyes, hands, and feet from physical trauma, and step 3 is taking care of themselves. The purpose of this research are to determine the relationship between the level of knowledge about leprosy with self-care in patients with leprosy in Sukoharjo district. Type of this research is quantitative. The method used is analytic with cross sectional approach. The subjects of the research were all leprosy patients which listed at each region work of all Community Health Center of Sukoharjo districts as many 37 respondents using total sampling. Data analysis used Spearman Rank (Rho) with significance level (α = 0.05) was obtained p value of 0.001 (p <0.05) that totaled Ho and Ha accepted. The conclusions that there is a correlation between the levels of knowledge about leprosy with self-care in patients with leprosy in Sukoharjo district. Obtained a correlation coefficient (r) 0.715 which indicates the strength of a strong connection. Keywords: Knowledge, Leprosy, Self Care.